9. DISEASE STRUCTURE AND MEDICAL EXAMINATION AND TREATMENT COSTS OF INPATIENTS AT THE TRAUMA SURGERY DEPARTMENT OF GENERAL HOSPITAL OF AGRICULTURAL IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: Description of disease structure and analysis of treatment and examination costs for inpatients at the Trauma Surgery Department of the General Hospital of Agricultural in 2023.Subjects and methods: Cross-sectional descriptive study design, extracting data from 5,406 inpatient cases from the HIS smart hospital system in the form of an electronic file.Results: According to ICD 10, chapter XIX (Poisoning damage and some consequences due to exogenous causes) accounted for the highest rate, accounting for 79.97%. Inpatients assigned to testing services account for the highest percentage (76.05%), while blood testing accounts for the lowest (4.38%). The highest structural costs are in medical supplies (43.14%), while the lowest are in outpatient services (0.89%). The highest cost is in chapter XIII with more than 16 million dong, the lowest in chapter XVIII is more than 1.7 million dong. The highest average drug cost per patient in chapter XII is 2,696,836.11 dong. The highest average bed cost per patient in chapter XII is 3,602,038.89 dong.Conclusions: The research results serve as the foundation for the hospital to develop a medical investment plan, estimate the types of drugs, medical supplies and consumables… that are appropriate and responsive to the disease model, as well as to establish policies for developing activities in compliance with regulations, combined with regular and timely inspections and supervision.
Keywords: ICD-10; costs; Trauma Surgery Department; General Hospital of Agricultural